Spindle Cell Hemangioma. A Case Report and Literature Review - Andrea González de Godos; María Belén Rodríguez Sanz; Carmen de la Cuesta de la Llave; Pilar Isabel González Márquez; Íñigo López de Cenarruzabeitía; Enrique Pastor Fuente; David Pacheco Sánchez (Revista Finlay)
Spindle cell hemangioma is a rare benign vascular tumor. It has been linked to Maffucci syndrome, Klippel-Trenaunay syndrome, and other venous malformations. They are usually purplish dermal nodules on the distal extremities of children and young adults, with no sex predilection. A case of a 22-years-old patient who suffered from a subcutaneous nodule, painful on pressure, in the right leg is presented. On physical examination, a 1.5 cm violaceous round tumor was observed. The presence of a hemangioma was suspected. A simple excision was performed and sent to the pathology department. The sample was described as an intraluminal nodule made up of a proliferation of spindle-shaped cells with moderate atypia and isolated mitotic figures, and the diagnosis of intravascular spindle cell hemangioma was confirmed. The diagnosis of spindle cell hemangioma is anatomopathological and simple excision is usually sufficient as treatment, although they frequently recur. Since spindle cell hemangioma is a little-known entity and can be confused with other vascular lesions, the communication of this case is considered interesting. Knowledge of this type of injury can increase reported cases.